Thermal and energy efficiency study of passive heating and cooling systems in Morocco's cold desert climate - Ali Lamrani Alaoui; Abdel-illah Amrani; Ahmed Alami Merrouni; Jamal-Eddine Salhi; Ouafae Boulerhcha; Abdelkarim Daoudia; Youssef El Hassouani; Elmiloud Chaabelasri; Mohammed Halimi (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
This research aims to showcase the imperative of integrating passive cooling and heating techniques within buildings to effectively decrease energy consumption. To accomplish this objective, numerical simulations were conducted on a representative double-walled brick building in two cold desert climates using TRNSYS software. The simulations were performed to compare and evaluate the thermal and energy performance of two distinct passive techniques, one for cooling the reflective roof and the other for heating the Trombe wall (TW). The findings demonstrate that employing a reflective roof building with an air gap significantly reduces indoor temperatures by 3 °C during the hottest weekdays of summer, as compared to the reference building, across the two studied Moroccan climates. Moreover, this approach decreases the demand for cooling energy by an impressive 69–78 %. Similarly, the passive heating technique proves highly effective during winter, reducing energy requirements by 26–30 % while increasing indoor temperatures by over 2.9 °C. Combining both techniques proves to be the most efficient solution, resulting in a 37.87 % reduction in total annual energy consumption for cooling and heating in Er-Rachidia and a 30 % reduction in Ifran. These results strongly support the suggestion that Moroccan thermal regulations should incentivize the adoption of passive cooling and heating systems, particularly in cold desert climates.